Topology Analysis of iBGP Confederation Case : Indonesia Research and Education Network (IdREN) - Irwin Wijaya Lahusen; Widyawan Widyawan; Sri Suning Kusumawardani (Faculty of Science and Technology, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
Implementation of the BGP Confederation topology scenario, found a number of new facts that influence the final decision making for BGP network managers. In previous studies it has been mentioned a number of factors that influence QoS from a topology scheme, among others, the number of Sub AS and the number of routers that make up the iBGP topology. In this study, a number of scenarios were developed by giving variants to bandwidth parameters and adding measurement parameters to Lost Datagram in all scenarios. The results obtained are quite significant, affecting QoS and finding a number of new facts related to the effect of using traffic generators. This research was tested on the Indonesia Research and Education Network (IdREN) network using GNS3.